Massachusetts Health Reform Cost Less and Was More Effective for Uninsured Individuals With Venous Thromboembolism: A Cost-Effectiveness Analysis. Issue 5 (May 2016) - Kapoor, Alok; Shaffer, Nicholas; Hanchate, Amresh; Roberts, Mark; Smith, Kenneth
Abstract : Background: Patients with venous thromboembolism (VTE) require access to comprehensive physician and pharmacy benefits to prevent recurrence and hemorrhage. Before 2006, Massachusetts provided these benefits through a program restricted to safety net hospitals called Free Care. Providing portable health insurance through Massachusetts health reform could improve outcomes for uninsured with VTE but its cost-effectiveness is unknown. Methods and Results: We constructed a Markov decision analysis model comparing our conceptualization of the Massachusetts health reform (health reform strategy) to no health reform strategy for a patient beginning warfarin for new episode of VTE. In the model, a patient may develop recurrent VTE or develop hemorrhage or stop warfarin after 6 months if no event occurs. To measure effectiveness, we analyzed laboratory data from Boston Medical Center, the largest safety net hospital in Massachusetts. Specifically, we measured the probability of having a subtherapeutic warfarin level for patients newly insured compared with those on Free Care prereform adjusting for secular trends. To calculate inpatient costs, we used the Health Care Utilization Project. We then calculated the incremental cost-effectiveness ratio for the health reform strategy adjusted to 2014 USD per quality-adjusted life-year (QALY) and performed sensitivity analyses. The health reform strategy cost less and gained more QALYs than the no health reform strategy. Our result was most sensitive to the odds that Health Reform protected against a subtherapeutic warfarin level, the cost of Health Reform, and the percentage of total health care costs attributable to VTE in Massachusetts. Conclusion: The health reform strategy cost less and was more effective than the no health reform strategy for patients with VTE. Abstract : Supplemental Digital Content is available in the text.